Rhetorics of self-making - Battaglia, Debbora (University of California Press, 1995)
This book advances the cross-cultural study of selfhood in three ways: First, it argues that selfhood is culturally situated and emergent in social practices of persuasion. Second, it demonstrates how postmodernity problematizes the experience and concept of the self. Finally, it challenges the pervasive practice of equating an individuated self with the Western world and a relational self with the non-Western world.